2015
DOI: 10.1039/c5cc07212c
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-oriented heterocyclic synthesis using divergent reactivity of N-substituted iso(thio)cyanates

Abstract: Carbon-substituted isocyanates and isothiocyanates are common building blocks in organic synthesis. In contrast, synthetic uses of N-substituted isocyanates and isothiocyanates are severely underdeveloped: few have been reported and their reactivity had not been compared. Herein, we compare the reactivity of blocked (masked) N-isocyanate and N-isothiocyanate precursors in cascade reactions. Divergent reactivity is observed with secondary propargylic and allylic systems, leading to new syntheses of imidazolones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Finally, we performed exploratory attempts toward three related cascades. These proved rewarding as we showed that: (1) imidazolidinone ( 7p ) formation was possible if ring closure was achieved via 1,4-addition (rather than 1,2-addition), using an α,β-unsaturated amino-ester as reagent; (2) an N -isothiocyanate precursor also engaged in a related cascade 14 to form an amino-thiohydantoin ( 7q ); (3) amide-substituted hydantoin ( 7r ) could be synthesized using an amido-isocyanate precursor. Collectively, this data suggested that a variety of N -isocyanate precursors could engage in cascade reactions and display similar reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we performed exploratory attempts toward three related cascades. These proved rewarding as we showed that: (1) imidazolidinone ( 7p ) formation was possible if ring closure was achieved via 1,4-addition (rather than 1,2-addition), using an α,β-unsaturated amino-ester as reagent; (2) an N -isothiocyanate precursor also engaged in a related cascade 14 to form an amino-thiohydantoin ( 7q ); (3) amide-substituted hydantoin ( 7r ) could be synthesized using an amido-isocyanate precursor. Collectively, this data suggested that a variety of N -isocyanate precursors could engage in cascade reactions and display similar reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…The desired N -isocyanates A are produced in situ upon heating or treatment with a base, in acetonitrile under microwave irradiation conditions ( Scheme 8 ). The reaction tolerated a variety of functional groups such as fluoro, cyano, hydroxy, and methoxy, allowing a further derivatization of the products [ 90 ].…”
Section: Reviewmentioning
confidence: 99%
“…While prior studies reported the reactivity of aminoisothiocyanates, the Beauchemin group investigated the reactivity of iminoisothiocyanates in the context of a cascade reaction with an aminoester, 65 and compared the reactivity in cascade reactions involving aminoisocyanates. 66 These reports are discussed in detail in the next section.…”
Section: Rearrangement Of Aminoisothiocyanatesmentioning
confidence: 99%
“…In addition to developing cycloaddition reactions, Beauchemin developed several cascade reactions using simple or amphoteric nitrogen nucleophiles. 65,66,77,78,80,81 This work also required improved control over N-isocyanate formation and reactivity.…”
Section: Review Syn Thesis Equation 22 Synthesis Of Pyrazolones By Wamentioning
confidence: 99%
See 1 more Smart Citation